'The wairua first brings you together': Māori experiences of meaningful connection in neurorehabilitation. Issue 1 (13th March 2022) - Wilson, Bobbie-Jo; Bright, Felicity A. S.; Cummins, Christine; Elder, Hinemoa; Kayes, Nicola M.
Abstract: Background and Aims: Therapeutic connections enhance patient experience and outcomes after neurological injury or illness. While we have some understanding of the components necessary to optimise therapeutic connections, these have developed from western-centric ideals. This study sought to explore the perspectives of Māori brain injury survivors, and their whānau (wider family and community), to develop more culturally informed understandings of what matters most for Māori in the development and experience of therapeutic connection. Design and Methods: A bicultural approach underpinned by principles of Kaupapa Māori Research was used. Whānau views and experiences were gathered through wānanga (focus groups). These perspectives were analysed drawing on Māori methods of noho puku (self-reflection), whanaungatanga (relational linkage) and kaitiakitanga (guardianship). Findings: Three wānanga were held with 16 people – 5 brain injury survivors and 11 whānau members. The phrase 'therapeutic connection' did not resonate; instead, people spoke of meaningful connections . For rehabilitation encounters to be meaningful, three layers of connection were acknowledged. The elemental layer features wairua (spirit) and hononga (connection) which both underpinned and surrounded interactions. The relational layer reflects the importance of whānau identity and collectivism, of being valued, known, and interactively spoken with. Finally, the experiential layer consists of relational aspects important within the experience: relationships of reciprocity that are mana-enhancing and grounded in trust. These layers are interwoven, and together serve as a framework for meaningful connections. Conclusions: Meaningful connections in neurorehabilitation are underpinned by wairua and hononga; are multi-layered; are enabled through interactions with people, practice, process and place; are inclusive of whānau and resonate with Māori worldviews. The primacy of wairua and whānau within an interconnected view of health, challenges individualistic notions inherent in western health models and deepens existing understandings of meaningful connections in neurorehabilitation which can guide future rehabilitation research, teaching and practice.